Correction: Effects of Chronic Fluoxetine Treatment on Neurogenesis and Tryptophan Hydroxylase Expression in Adolescent and Adult Rats - Klomp, Anne; Václavů, Lena; Meerhoff, Gideon F.; Reneman, Liesbeth; Lucassen, Paul J. (PLOS ONE, 2015)
null